Moisture enhances the positive effect of leaf-cutting ant refuse dumps on soil biota activity - Fernandez, Anahi Rocio (2013)
Soil biota activity in arid lands is often limited by the availability of water and organic matter. We experimentally explored whether small changes in soil moisture affect the activity of soil biota in external refuse dumps of the leaf-cutting ant Acromyrmex lobicornis, one of the most important sources of organic matter in a semi-arid land of north-western Patagonia. We estimated CO2 consumption in refuse dumps and in adjacent, non-nest soil samples at two moisture levels, after 48 and 72 h. Soil biota activity, estimated by respiration rates, was up to 160 times greater in refuse dumps than in adjacent, non-nest soils. Activity of soil biota in non-nest soil did not change through time and was not affected by moisture. Conversely, soil biota increased their activity in refuse dump samples only at high moisture condition after 72 h. As the activity of microorganisms is key for soil nutrient generation and availability, refuse dumps may be considered as ‘islands of fertility’ for plants. This effect may be especially important after sporadic spring rainfalls, when the beneficial effect of refuse dumps on soil biota is enhanced. In addition, as refuse dumps generate several times more CO2 than non-nest soils, nest areas may be considered also as hot spots of CO2 emissions. These results illustrate the potential importance of ant nests for nutrient cycling, maintenance of plant cover and carbon balance in arid ecosystems.